2021
DOI: 10.3389/fpls.2021.781987
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Petal and Leaf Wax Deposition Affects Cuticular Transpiration in Cut Lily Flowers

Abstract: The vase life of cut flowers is largely affected by post-harvest water loss. Cuticular wax is the primary barrier to uncontrolled water loss for aerial plant organs. Studies on leaf cuticular transpiration have been widely conducted; however, little is known about cuticular transpiration in flowers. Here, the cuticular transpiration rate and wax composition of three lily cultivars were determined. The minimum water conductance of tepal cuticles was higher at the green bud than open flower stage. Lily cuticular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
3
11
1
Order By: Relevance
“…Buschhaus et al (2015) found that the effectiveness of the C. bipinnatus petal cuticle in blocking water transport was only one‐tenth of that of the leaf cuticle. Similarly, in our previous studies on rose and lily, the water permeance of the petals was higher than that of leaves (Cheng et al, 2019, 2021). The water permeance of lily petals was 5.5 × 10 −5 m s −1 (‘Huang tianba’) and 1.3 × 10 −4 m s −1 (‘Tiber’), whereas the minimum conductance of the leaves was lower, at 2.2 × 10 −5 m s −1 (‘Huang tianba’) and 1.5 × 10 −5 m s −1 (‘Tiber’).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Buschhaus et al (2015) found that the effectiveness of the C. bipinnatus petal cuticle in blocking water transport was only one‐tenth of that of the leaf cuticle. Similarly, in our previous studies on rose and lily, the water permeance of the petals was higher than that of leaves (Cheng et al, 2019, 2021). The water permeance of lily petals was 5.5 × 10 −5 m s −1 (‘Huang tianba’) and 1.3 × 10 −4 m s −1 (‘Tiber’), whereas the minimum conductance of the leaves was lower, at 2.2 × 10 −5 m s −1 (‘Huang tianba’) and 1.5 × 10 −5 m s −1 (‘Tiber’).…”
Section: Discussionsupporting
confidence: 72%
“…They found that the petal cuticle showed weaker water resistance than the leaf cuticle because the chain lengths of the main components of the petal cuticle were shorter than those in the leaf cuticle. Similar findings have been made in rose and lily (Cheng et al, 2019, 2021). Goodwin et al (2003) studied the wax composition of snapdragon petals over 12 days from flower opening to senescence and found no significant change during flower development.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…It remains unclear to what extent the flowers contribute to the differences in thrips resistance among the accessions. Flowers and leaves differ in their morphology, e.g., cuticular wax layers [ 31 , 32 ] and chemical composition [ 33 ]. This suggests that leaf and flower resistance levels may differ considerably, and therefore, total plant resistance might not be directly derived from assessing leaf resistance alone.…”
Section: Introductionmentioning
confidence: 99%
“…Lily, Lilium spp., belongs to the genus Lilium of the family Liliaceae, which is one of the most popular perennial herbaceous bulbous plants widely grown in temperate, subtropical, and tropical regions with various food, aesthetic, economic and medicinal values [1][2][3]. Lilies are a commercially signi cant cut ower worldwide due not only to their elegant shape but also to their appealing scent known for its variations in color, pattern and shape, which is one of the six major bulb owers and shares a great part of the commercial market of the owers worldwide [4][5][6].…”
Section: Introductionmentioning
confidence: 99%